TINJAUAN VISUAL THINKING MATERI STATISTIKA BERDASARKAN GAYA BELAJAR SISWA SEKOLAH MENENGAH PERTAMA - Purwasih, Yuliana; Harrtoyo, Agung; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out the visual thinking of students who have visual, auditory, or kinesthetic learning style for statistic material especially in the statistical data presentation sub-topic in Junior High School Pontianak. The research method used in this study was descriptive method. The study subjects were 32 students from class IX B. The subjects of this research were determined based on the students’ learning style and the consideration of the math teacher. The data analysis result showed total 37,5% students have visual learning style, 37,5% students have auditory learning style and 25% students have kinesthetic learning style. Overall, the visual thinking of students’ who have visual, auditory or kinesthetic learning style is in low category. Kata Kunci: Visual Thinking, Learning Style, Statistic